Influence of follicular fluid thyroid stimulating hormone on laboratory indicators of assisted reproductive technology - WANG Xue-ying, GUO Wei, XIE Cong-cong, YAO Guan-feng, GUO Xiao-li, HE Wei, LIU Xiao-qun (Jichu yixue yu linchuang, 2020)
Objective To evaluate the association between thyroxin(TH) level and thyroid stimulating hormone (TSH) in follicular fluid (FF) and in serum and whether TSH affects laboratory indicators predicting assisted reproductive technology outcomes. Methods This study enrolled 142 women undergoing ART. According to the concentration of TSH in follicular fluid, the volunteers were divided into three groups: TSH＜2.5 mIU/L (group A), 2.5≤TSH＜4 mIU/L (group B) and TSH≥4 mIU/L (group C). Blood samples on day 2 or 3 of menstruation and the first tube of clear, blood free follicular fluid on the day of retrieval oocytes were collected to detect the levels of TSH, fT4 and fT3 with electrochemical luminescence method. Results 1)The average number of eggs obtained in group A was significantly lower than group B and group C, that of group B was significantly lower than that in group C (P＜0.05); The rate of MII in group C was significantly lower than that in group A and group B(P＜0.05); The fertilization rate of ICSI in group B was significantly higher than group A and group C (P＜0.05);The available embryo rate in group C was significantly lower than group A and group B (P＜0.05); However, the blast cyst utilization rate in group C was significantly higher than that in group A and group B (P＜0.05). 2)There was a positive correlation between TSH concentration in follicular fluid and blood concentration (P＜0.05), and between TSH concentration in follicular fluid and fT3 concentration (P＜0.05). Conclusions TSH level in follicular fluid is positively correlated with TSH level in basal serum. TSH ≥ 4 mIU/L in follicular fluid on the day of oocyte retrieval may have some effects on ART outcome.